Nutritional status, nutrient accumulation and yield of corn grown in Yellow-Red Oxisol - Oliveira, Mauro Wagner de; da Silva, Vinicius Santos Gomes; Soares, Andréa Renilda Silva; Oliveira, Terezinha Bezerra Albino; Silva, Denise de Santana; Machado, Polyana Albino Silva (Revista Geama, 2020)
Corn extracts and accumulates high amounts of soil nutrients due to its high forage yield. The aim of this study was to evaluate nutritional status, nutrient accumulation, and forage yield of corn hybrid BM 3066 PRO2, as well as primary macronutrient balance in the soil-plant system. Thus, a systematic sampling was carried out in seven crop areas of corn grown in a Yellow-Red Oxisol. Plants did not show nutrient deficiency. Leaf contents had the following decreasing order of concentration N> K> Ca> P> S> Mg> Fe = Mn> Zn> B> Cu. Biometric evaluations were carried out and we found average plant height and first ear insertion height of 2.42m and 1.52m, respectively. Fresh and dry biomass yields were 57.17 and 18.36 t ha-1, respectively. The accumulation of primary macronutrients in plant shoot biomass was 235.95 kg ha-1 N, 36.99 kg ha-1 P and 225.53 kg ha-1 K. Nutrient balance was positive for nitrogen (9.1 kg) and phosphorus (22 kg), but negative for potassium (-15 kg).